The role of low-grade infection in the pathogenesis of apparently aseptic tibial shaft nonunion. Issue 11 (November 2021) - Hackl, Simon; Keppler, Lena; von Rüden, Christian; Friederichs, Jan; Perl, Mario; Hierholzer, Christian
Abstract: Purpose: Aim of this study was to determine the rate of low-grade infection in patients with primarily as aseptic categorized tibial shaft nonunion and lack of clinical signs of infection. Methods: In a retrospective study between 2006 and 2013, all patients who underwent revision surgery for treatment of tibial shaft nonunion without clinical evidence of infection were assessed. Bacterial cultures harvested during nonunion revision, C-reactive protein (CRP) and/or white blood cell (WBC) values at hospital admission, outcome, and epidemiological data were analyzed. Results: In 88 patients with tibial shaft nonunion without any clinical signs of infection, bacterial samples remained negative in 51 patients. In 37 patients, microbiological diagnostic studies after long-term culturing demonstrated positive bacterial cultures whereas after short-term culturing for 2 days only 17 positive cultures were observed. In 12 cases a mixed culture with 2.3 different bacteria on average was detected. Among patients with negative bacterial cultures bone healing was achieved after 13.2 months. Nonunion with positive bacterial cultures required 19 (range 2-42) months until osseous healing ( p = 0.009). Furthermore, nonunion with positive bacterial cultures require statistically more surgical revisions to achieve healing (2.9 ± 0.5 vs. 1.3 ± 0.1 additional procedure; ( p = 0.003). Hematological studies carried out before surgical intervention did not demonstrate significant differences in CRP values (negative vs. positive cultures: 0.3 (range 0.3-2.8) mg/dl vs. 0.5 (range 0.3-5.7) mg/dl ( p = 0.181) and in WBC values (negative vs. positive cultures: 7.4 (range 3.5-11.9) /nl vs. 7.3 (range 3.7-11.1) /nl ( p = 0.723). Limitations of this study may include the varying amount of the at least four samples for microbiological diagnostics as well as the circumstance that for diagnosing low-grade infection swabs and tissue samples were included in this evaluation as being equivalent. Conclusion: The pathogenesis of nonunion may originate from low-grade infection even in patients without clinical signs of infection. In addition, nonunion with positive bacterial cultures require statistically more surgical revisions to achieve healing. Therefore, during any revision surgery, multiple bacterial samples are intended to be harvested for long-term culturing. Particularly, in tibial shaft nonunion following Gustilo-Anderson type III open fractures, low-grade infection should be suspected. Trial registration number: DRKS00014657. Date of registration: 04/26/2018 retrospectively registered